2008
DOI: 10.1007/s00586-008-0747-1
|View full text |Cite
|
Sign up to set email alerts
|

New concept for backache: biopsychosocial pain syndrome

Abstract: Recently a new concept for explaining backache, ''biopsychosocial pain syndrome,'' has been suggested. Psychosocial factors play an important role in the development and persistence of backache from an early stage. Diagnosis and treatment of backache should be based on the new concept. A good relationship between doctors and patients influences treatment outcome and patient satisfaction. Treatment should be decided by patients themselves, after being informed of the natural history of the disease and the merit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 59 publications
1
21
0
3
Order By: Relevance
“…Data from Austria showed that musculoskeletal pain was strongly associated with work pressure, social distress in the workplace, sexual dissatisfaction, and discomfort in family or in partnership [18]. Additional social factors associated with back pain are occupational distress or job loss [7].…”
Section: Prevalence Of Back Painmentioning
confidence: 98%
See 2 more Smart Citations
“…Data from Austria showed that musculoskeletal pain was strongly associated with work pressure, social distress in the workplace, sexual dissatisfaction, and discomfort in family or in partnership [18]. Additional social factors associated with back pain are occupational distress or job loss [7].…”
Section: Prevalence Of Back Painmentioning
confidence: 98%
“…Furthermore, obesity as example for a biological factor is associated with back pain [8]. Psychological factors, especially common mental disorders such as anxiety and depression, are very well examined [7]. In Europe, 21 % of subjects with chronic pain reported also to have been diagnosed with depression [4].…”
Section: Factors Associated With Back Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial infection was also reported as a cause of low back pain, separately from the causes originated from spinal column 13) . Diagnosis should be made considering geographical or cultural differences, and biopsychosocial factors, not only morphological abnormalities, as a cause of low back pain [14][15][16] .…”
Section: The Cause Of Low Back Painmentioning
confidence: 99%
“…However, the contribution of psychosocial factors to the development of classic "somatic" disorders is widely accepted. For example, in the case of backache, work perception (occupational stress, intensity of concentration, satisfaction, job loss) and psychosocial factors (anxiety, depression, self-control, marital status) play a major role in addition to biological factors such as nerve-root compromise [28]. We found that joint and muscle pain and sexual dissatisfaction showed a strong relationship with discomfort in family/partnership in both sexes; joint and muscle pain were also strongly related to social stress in the workplace in men.…”
Section: Discussionmentioning
confidence: 99%